GC-MS and FTIR analysis of methanolic leaf extract of Rhynchosia minima (L.) DC. - Patil, Vilas T.; Jadhav, Varsha D. (Current Botany, 2021)
The current analysis was carried out to determine the chemical components in the leaves of R. minima (L.) DC. The GC-MS analysis of methanolic leaves extract of R. Minima indicated the presence of 19 compounds. The prevailing compounds of R. minima leaves were 1Pentadecene (14.31), alpha. Bisabolol (10.39%), 1Heptadecene (9.78%), Cyclohexene,4 (1,5dimethyl1,4hexadienyl (7.06%), 3Hexadecene (Z) (8.10%), Caryophyllene (6.58%), Neophytadiene (5.16%), Humulene (1.91%), Naphthalene,1,2,3,5,6,8 a-hexahydro-4,7-dimethyl (3.72%), Hexadecanoic acid, methyl ester (2.09%), Pentadecanone (3.13%), 8-Octadecanone (4.02%),1-Nonadecene (4.16%), Spiro[4.5]dec-6-en-8-one,1,7-dimethyl-4-(1-methylethyl (2.97%), Neophytadiene (2.24%),(E)-. beta.-Famesene (1.92%), Cyclohexene,4-[(1E)-1,5-dimethyl-1,4-hexadien (1.80%), Cyclohexane,octyl (1.45%), beta Bisabolene (9.21%). These compounds have antibacterial, antifungal, antioxidant, hemolytic, insecticidal, and lubricant activity. Fourier Transform Infra-Red Spectroscopy (FTIR) leaf anlysis of R. minima shows lipid, protein, phosphate ion, carboxylic acid, hydroxy compound, aliphatic bromo compounds. The present study revealed that R. minima leaves represent various types of bioactive compounds. 1-Heptadecene with antibiotic activity, 8-Octadecanone shows antimicrobial activity and hexadecanoic acid, nematicide, antibiotic, antioxidant, hypocholesterolemic production of methyl ester.